Impact of the Coronavirus epidemic (COVID-19) on the mental health of health workers and general population in China - Lozano-Vargas, Antonio (2020)
In the fight against the Coronavirus (COVID-19), health workers may experience mental health problems such as stress, anxiety, depressive symptoms, insomnia, denial, anger and fear. In a study in China, anxiety among health workers reached a 23.04%, with higher levels among women than men, and also higher among nurses than doctors. Likewise, in the general Chinese population, there was a moderate to severe psychological impact of 53.8%, with 16.5% of depressive symptoms, 28.8% of anxiety symptoms and 8.1% of stress, all of them between moderate to severe. Factors associated with a high psychological impact and high levels of stress, anxious and depressive symptoms were female sex, being a student, and having specific physical symptoms and a poor perception of their own health. Another study in China detected 35% of psychological distress in the general population, women presenting it more than men as well as the groups of 18-30 and over 60 years of age. The pandemic challenges us to take care of the health workers’ mental health as much as of the general population’s. Thus, the use of brief screening mental health scales, validated in our population, would be very effective to face the current public health challenges in our country.